1954
DOI: 10.1021/ja01653a015
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain Crystallization of n-Alkyl Polymethacrylates and Polyacrylates1

Abstract: In this study of side chain crystallinity, methacrylate and acrylate monomers, with «-alkyl groups containing from 12 to 18 carbon atoms, were synthesized, polymerized and copolymerized; dilatometric measurements were made on these polymers to determine the changes in specific volume with temperature and time; spacings were obtained from Debye-Scherrer patterns taken at small and wide angles. The following results were noted: the specific volume-temperature plots were S-shaped, typical of first-order transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 1 publication
8
82
0
Order By: Relevance
“…The diagrams show that most of the characteristic peaks of the monomer disappear rapidly as the irradiation dose increases, but a broad weak peak at 28= 6.8° and a sharp intense peak at 28 = 21.4 o, which correspond to the spacings of 13.0 and 4.2 A, respectively, remain even after the monomer is converted almost completely to polymer. Since the single intense line corresponding to a spacing of 4.2 A, is similar to that observed in vinyl stearate 5 and also in polymers derived from the vinyl stearate 14 and long-chain alcohol esters of acrylic and methacrylic acid, 15 the irradiated ODMA which has been converted to poly(ODMA) is considered to maintain an ordered structure due to paraffin-like crystallites. The diffuse 13 A reflection is not so easily interpreted.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 56%
“…The diagrams show that most of the characteristic peaks of the monomer disappear rapidly as the irradiation dose increases, but a broad weak peak at 28= 6.8° and a sharp intense peak at 28 = 21.4 o, which correspond to the spacings of 13.0 and 4.2 A, respectively, remain even after the monomer is converted almost completely to polymer. Since the single intense line corresponding to a spacing of 4.2 A, is similar to that observed in vinyl stearate 5 and also in polymers derived from the vinyl stearate 14 and long-chain alcohol esters of acrylic and methacrylic acid, 15 the irradiated ODMA which has been converted to poly(ODMA) is considered to maintain an ordered structure due to paraffin-like crystallites. The diffuse 13 A reflection is not so easily interpreted.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 56%
“…In both cases a reversible change in the spectra was observed at about 35°C to 40 0c. This temperature corresponds to the melting of the side chains in the bulk material 13)• The rather broad feature between 3 500 cm -1 and 3 000 cm -1 seen in some IR spectra is due to water which condenses on the cold MCT-B detector element. …”
Section: Interesting Phenomenamentioning
confidence: 99%
“…Rehberg and Fisher studied the brittle points of polyacrylates and poly(methacrylates) and found that upon an increase in carbons within the alkyl side chain the brittle points decrease up to 8 carbons for acrylates and 12 carbons for methacrylates, above which the brittle points increased. 13 This was attributed to the increase in the melting point of the side chains 14,15 Jordan et al investigated the crystallinity of the alkyl side chains in poly(n-alkyl acrylates) and they established that only the outer methylene units contributed to the crystal lattice. 16,17 This was also independently confirmed by several other investigators, it was proposed that the 8-9 methylene units closest to the polymer backbone do not contribute to the side chain crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 This was also independently confirmed by several other investigators, it was proposed that the 8-9 methylene units closest to the polymer backbone do not contribute to the side chain crystallinity. 15,18,19 Thus for both semi-crystalline poly(alkyl acrylate)s and poly(alkyl methacrylate)s the longer the side chain the higher the Tm of the poly(alkyl(meth)acrylate). 15,16 Furthermore it has been demonstrated that by copolymerising (meth)acrylate monomers the Tm of the resultant statistical copolymers can be manipulated to occur within a given range typically between the Tm values of the two homopolymers, with the exact value dependent upon the ratio of monomers within the structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation